A new species and new records of Hoplitis Klug (Hymenoptera, Megachilidae) from Russia - Alexander V. Fateryga; Maxim Yu. Proshchalykin; Evgeny V. Abakumov (Journal of Hymenoptera Research)
Hoplitis (Hoplitis) andreasmuelleri sp. nov., a member of the H. adunca species group, is described from the vicinity of Kurush (Samurskiy National Park, Dagestan, Russia). The new species is closely related to H. dagestanica Fateryga, Müller & Proshchalykin, 2023. Females of H. andreasmuelleri can be easily distinguished from those of H. dagestanica by a black antenna, a small impunctate triangular area at the base of the clypeus, ferruginous tarsi, sparse and often interrupted apical band of hairs on terga 1–5, and a whitish scopa. Males of H. andreasmuelleri can be easily distinguished from those of H. dagestanica by a black antenna, the last antennal article not tapering towards the apex, antennal articles 5–12 not modified, ferruginous tarsi, and the lateral lobes of the bilobed membranous appendage at the apical margin of sternum 6 laterally elongated into a rounded tip and medially not separated from each other by an emargination. Females of H. andreasmuelleri were recorded at flowers of two species of the genus Vicia L. (Fabaceae). Hoplitis (Kumobia) abbreviata (Morawitz, 1875) is reported from Russia (Altai Republic) for the first time. New distributional records are reported for H. (Alcidamea) fulva (Eversmann, 1852) and H. (Anthocopa) perezi (Ferton, 1894). Hoplitis (Anthocopa) papaveris (Latreille, 1799) is excluded from the fauna of Crimea and the south of European Russia from where it was previously reported based on a misidentification of H. perezi. The biology of H. perezi in Crimea is briefly discussed. An updated distributional list of all 39 species of Hoplitis known from Russia is provided.